(untitled) (International Journal of Environmental Sciences, 2025)
The natural characteristics of Muthanna Governorate, particularly the climatic conditions and the nature of the soil, have contributed to the occurrence of dust storms and their increasing frequency in recent years, which have had a significant impact on the expansion of various forms of desertification. The study area is characterized by a desert climate, with high temperatures throughout most of the year, minimal and irregular rainfall, which contributes to soil dryness, fragmentation, and susceptibility to wind erosion. Al-Muthanna Governorate experiences an increased frequency of dust phenomena, particularly at the end of winter and the beginning of summer months. This is attributed to rising temperatures and the cessation of rainfall, leading to soil heating and atmospheric disturbances that lift dust and particles to varying heights and distances, forming dust weather phenomena. Desertification in the study area manifests in various forms, with significant environmental and economic impacts. These include wind erosion of the soil, which varies seasonally and spatially across the governorate, as well as sand dunes occupying large areas and forming two main belts. These dunes pose serious risks by encroaching on agricultural lands, roads, and water channels, and serve as a source for sand and dust storms. Additionally, the issue of soil salinization is widespread, with the study showing that salinization is more concentrated in the sedimentary plain soils compared to the soils of the western plateau.